2010
DOI: 10.1007/s10661-010-1734-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DEM mesh size on AnnAGNPS simulation and slope correction

Abstract: The objective of this paper is to study the impact of the mesh size of the digital elevation model (DEM) on terrain attributes within an Annualized AGricultural NonPoint Source pollution (AnnAGNPS) Model simulation at watershed scale and provide a correction of slope gradient for low resolution DEMs. The effect of different grid sizes of DEMs on terrain attributes was examined by comparing eight DEMs (30, 40, 50, 60, 70, 80, 90, and 100 m). The accuracy of the AnnAGNPS stimulation on runoff, sediments, and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Shuttle Radar Topographic Mission has been considered a good global elevation data set, with overall quality sufficient for hydrologic model applications (Ludwig & Schneider, ). The effect of resolution of the digital elevation model (DEM) on terrain attributes within an AnnAGNPS model simulation has little impact on runoff, as it does not vary much with a decrease in DEM resolution; on the contrary, SL can change prominently, as DEM resolution has a significant impact on slope gradient (Wang & Lin, ). Hancock et al () found that area–slope and area–elevation (hypsometry) properties are well depicted by the DEMs at 90‐m resolution.…”
Section: Methodsmentioning
confidence: 99%
“…Shuttle Radar Topographic Mission has been considered a good global elevation data set, with overall quality sufficient for hydrologic model applications (Ludwig & Schneider, ). The effect of resolution of the digital elevation model (DEM) on terrain attributes within an AnnAGNPS model simulation has little impact on runoff, as it does not vary much with a decrease in DEM resolution; on the contrary, SL can change prominently, as DEM resolution has a significant impact on slope gradient (Wang & Lin, ). Hancock et al () found that area–slope and area–elevation (hypsometry) properties are well depicted by the DEMs at 90‐m resolution.…”
Section: Methodsmentioning
confidence: 99%
“…The h represents the vertical height of the slope, and l represents the horizontal distance of the slope. According to the rules of the International Geographical Union Commission on Geomorphological Surveys and Geomorphological Mapping, the slope was divided into six grades [ 40 ]: 0–5° (ground), 5–15° (gentle slope), 15–35° (incline slope), 35–55° (slanted slope), 55–70° (steep slope), and 70–89.9° (rapidly steep slope).…”
Section: Methodsmentioning
confidence: 99%
“…The spatial resolution of the DEM has little impact on AnnAGNPS runoff volume estimates [11,41], but soil erosion and sediment loads can change with DEM resolution, since resolution impacts slope [42]. LIDAR-derived 3-m DEMs should improve the model performance in the study watershed compared with applications that use more-commonly available 10 m or 30 m resolution DEMs.…”
Section: Methodsmentioning
confidence: 99%